Expression of PCNA, CD-31 and HER-2 in Serbian patients with oral squamous cell carcinoma - Lončarević, Slobodan A.; Brajković, Denis O.; Gardašević, Milka F.; Lončarević, Olivera Lj.; Lađević, Nebojša G.; Nešić, Dejan M.; Stamenković, Dušica M.; Likić-Lađević, Ivana S.; Lađević, Nikola N.; Rančić, Nemanja K. (Archives of Biological Sciences, 2019)
Paper description: Tumor markers are significant for early detection of (pre)malignant lesions, local recurrence and distant metastasis, prevention of secondary tumors, appropriate therapeutic protocol choice, and as a prognostic factor for disease progression. In this prospective case, immunohistochemical expression of the tumor markers PCNA, HER-2 and CD-31 in patients with oral squamous cell carcinoma undergoing the same surgical treatment during a ten years period was determined. Increased expression of PCNA during advanced stage of the disease may be a useful biomarker in determining further disease progression. PCNA can be useful in routine clinical practice. Abstract: Several studies have investigated the expression of tumor markers, including p53, HER-2, PCNA, EGFR, VEGFR CD-31 and Bcl-2 in patients with oral squamous carcinoma (OSC). This study aimed to determine the expression of proliferating cell nuclear antigen (PCNA), endothelial functions of platelet/endothelial cell adhesion molecule-1 (CD31) and human epidermal growth factor receptor-2 (HER-2) according to OSC stage. The prospective study included 62 patients diagnosed with OSC stages II and III. Surgical specimens were obtained from tumor and peritumoral tissues. We determined the pathohistological degree of tumor differentiation and the immunohistochemical expression of PCNA, CD-31 and HER-2 for each specimen. Immunohistochemical analysis of the expression of PCNA in tumor cells demonstrated poor staining of immunoreactive tumor cells in 23 patients (10 in stage II, 7 in stage IIIa and 6 in stage IIIb). Moderately expressed PCNA-immunoreactivity in the tumor cells in 17 patients (7 in stage II, 6 in stage IIIa and 4 in stage III), and extremely strong PCNA-immunoreactive staining in tumor cells of 10 patients with IIIb stage, was observed. These results suggest that PCNA expression combined with pathohistological findings could possess a prognostic value in determining the survival rates for patients with oral squamous cell carcinoma. https://doi.org/10.2298/ABS190705053L Received: July 5, 2019; Revised: August 4, 2019; Accepted: August 6, 2019; Published online: August 30, 2019 How to cite this article: Lončarević SA, Brajković DO, Gardašević MF, Lončarević OLj, Lađević NG, Nešić DM, Stamenković DM, Likić-Lađević IS, Lađević NN, Rančić NK. Expression of PCNA, CD-31 and HER-2 in Serbian patients with oral squamous cell carcinoma. Arch Biol Sci. 2019;71(4):703-10.